THE ROLE OF FORENSIC ACCOUNTING IN REDUCING THE EFFECTS OF CREATIVE ACCOUNTING IN THE FINANCIAL STATEMENTS OF IRAQI BANKS - falyyih, Hawraa; alkhafagi, Hussein thamer; Abdulrasool, Mohammed; mardan, Dr.zaid ayed (The journal of contemporary issues in business and government, 2023)
The research aims to highlight the importance of forensic accounting and to identify the role that forensic accountants play in limiting creative accounting practices when preparing financial statements. Therefore, the researcher relied on the descriptive approach. This research has reached several results most notably that the activities practiced by forensic accounting in relation to risk management in economic units have a weak impact in limiting creative accounting practices. The research also presented a set of recommendations, the most important of which was the need to generalize the idea of judicial accounting to economic units, courts, judges and the law in order to contribute to rationalizing their decisions and to provide reasonable assurances about the absence of distortions in the financial statements and accounting reports issued.